Rapsódia sergipana : estações de leitura e produção textual numa perspectiva do ensino híbrido na educação de jovens e adultos - Silva, Janes Santos (2017)
It has long been observed that new technologies have brought transformations to society and with it new ways of interacting and transmitting knowledge, as well as collaborating effectively with the teaching and learning processes. In this context, hybrid education emerges as an innovative practice in education, presenting a pedagogical approach that combines classroom activities with activities carried out through the technologies. In our research, we intend to demonstrate how this kind of teaching, which mixes the classroom with the virtual, adapting the conventional classroom to the new technologies, can be used in the personalization of teaching and learning actions. For that, we proposed to elaborate a set of activities based on the combination of face-to-face and online moments, starting with the poem Rapsódia Sergipana by Stella Leonardos, in order to resize the traditional methodology, and present a type of innovative learning which uses hybrid teaching, in the "rotation by seasons" model, to be worked with a class of Elementary School students in the EJA modality, IV stage (or 9th grade). In this hybrid lesson proposal, the poem Rapsódia Sergipana by Stella Leonardos, in addition to rescuing the Sergipe culture, will also serve as a basis for the construction of an example of a hybrid classroom where the teacher can contribute to the education of young people and adults. diversity of groups, and can put into practice the personalization of teaching, using new technologies, considering that today's society is seen as the information society, and in it the Internet establishes new forms of communication, it is up to the school to provide the this new generation tools to build new senses through virtuality. (MARCUSCHI, 2010). Authors and authors such as Stephanou and Bastos (2005), Lima and Moura (2015), Bacich (2015), and Christensen, Horn & Staker (2017), among others, integrate the theoretical basis of our approach.